Pembuatan Buku Pelajaran Digital Berbasis Canva sebagai Penunjang Pembelajaran Jarak Jauh pada SMP Kosgoro, Sragi - Siska, Astri Iga; Kareja, Novilia; Meidayanti, Karina (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Encouraged by the enthusiasm of the teachers to continue to improve existing learning models in order to increase students' enthusiasm for learning, the team of communal service provides solutions that can be used to continue to support teaching and learning activities. The solution presented is the creation of a Canva-based digital learning book. The service activity was carried out at Kosgoro Middle School, Sragi from June – September 2022. The method used was training and assistance in making Canva-based digital textbooks. The activity stages consist of preparation, introduction to Canva, training and assistance in making digital textbooks and evaluation. The results obtained through this service activity are that participants gain knowledge and skills related to the creation of Canva-based learning media, participants are also enthusiastic during the activity and directly apply it to the subjects taught.